De novo variants in Myelin regulatory factor (MYRF) as candidates of a new syndrome of cardiac and urogenital anomalies. Issue 4 (15th February 2018) - Pinz, Hailey; Pyle, Louise C.; Li, Dong; Izumi, Kosuke; Skraban, Cara; Tarpinian, Jennifer; Braddock, Stephen R.; Telegrafi, Aida; Monaghan, Kristin G.; Zackai, Elaine; Bhoj, Elizabeth J.
Abstract : Myelin Regulatory Factor (MYRF) is a transcription factor that has previously been associated with the control of the expression of myelin‐related genes. However, it is highly expressed in human tissues and mouse embryonic tissues outside the nervous system such as the stomach, lung, and small intestine. It has not previously been reported as a cause of any Mendelian disease. We report here two males with Scimitar syndrome [MIM 106700], and other features including penoscrotal hypospadias, cryptorchidism, pulmonary hypoplasia, tracheal anomalies, congenital diaphragmatic hernia, cleft spleen, thymic involution, and thyroid fibrosis. Gross neurologic functioning appears to be within normal limits. In both individuals a de novo variant in MYRF was identified using exome sequencing. Neither variant is found in gnomAD. Heterozygous variants in MYRF should be considered in patients with variants of Scimitar syndrome and urogenital anomalies.